Dividing Latin American activist labour in post-Brexit Britain. (1st June 2020) - Medden, Stephanie
This article describes how Latin American advocacy and activist groups operating in the United Kingdom engage in identity work through their collaboration with one another, the creation of discourses around cultural identity and the division of activist labour. By examining how the members of these groups plan their strategies, collaborate and use digital platforms to perform and construct identity, mobilize support and partner with ally groups, the author sheds light on some ways in which identity movements facing the threat of geopolitical shifts, such as Brexit, participate in identity work under precarious conditions. This article demonstrates how a bifurcation of activist labour represents two different but concurrent approaches to identity work for Latin American activists in post-Brexit Britain. It argues that such precarity challenges the primacy of Latinidad as a strategic resource for activists and, instead, encourages alternative forms of solidarity.